UMP Research Leaders Are Golden Globe Tigers - UMP, PNC (2019)
Kuala Lumpur, 26 April- Assistant Vice- Chancellor (Corporate and Quality Affairs), Professor Dato’ Dr. Mashitah Mohd. Yusoff and Dean of Faculty of Engineering Technology, Professor Dato’ Dr. Zularisam Abd. Wahid were recipients of the Golden Globe Tigers Awards 2019. Professor Dato’ Dr. Mashitah has won the The Golden Globe Tigers Award 2019 for Education Leadership Award meanwhile Professor Dato’ Dr. Zularisam for The Best Professor in Engineering Technology Studies.